Early expression changes of complement regulatory proteins and C5a receptor (CD88) on leukocytes after multiple injury in humans - Amara, Umme; Kalbitz, Miriam; Perl, Mario; Flierl, Michael A.; Rittirsch, Daniel; Weiss, Manfred; Schneider, Marion; Gebhard, Florian; Huber-Lang, Markus (Shock, 2010)
As a crucial element of innate immunity, the complement cascade becomes activated after severe trauma. Regulation of the complement cascade and protection against complement-mediated tissue destruction is provided by a selection of soluble and membrane-bound complement regulatory proteins (CRegs). To date, the leukocyte expression profile of CRegs in multiple injured patients is unknown. In the present study, expression of CRegs and the C5a receptor (CD88) was analyzed on neutrophils, monocytes, and lymphocytes by flow cytometry. Whole blood samples were obtained from healthy volunteers (n = 16) or multiple injured patients (n = 12) on admission in the emergency department and 4, 12, 24, 120, and 240 h after trauma. The content of CRegs and CD88 on leukocytes was significantly altered posttrauma: CD55 (decay accelerating factor) displayed a time-dependent, elevated expression pattern on neutrophils and monocytes, but not on lymphocytes. CD59 (membrane attack complex inhibitor) expression was significantly increased on neutrophils and monocytes at the time of admission and after 5 to 10 days in lymphocytes. CD46 (membrane cofactor protein) was significantly down-regulated in all three cell types posttrauma. CD35 (complement receptor 1) expression on neutrophils was initially decreased, whereas monocytes presented a significant increase in CD35 expression. CD35 on lymphocyte remained unchanged throughout the observation period. CD88 expression was considerably reduced on leukocytes between 0 and 240 h after injury. CD59, CD46, and CD88 expression values on neutrophils reversely correlated with severity of injury. In summary, expression profiles of CRegs and CD88 on leukocytes are specifically altered after polytrauma in humans, indicating a trauma-induced "complementopathy.". Copyright © 2010 by the Shock Society.
CRIS-Team Scopus Importer:2020-12-21
Keywords: C5aR; CD35; CD46; CD55; CD59; Complement; Polytrauma